Clinical evaluation of dragon’s blood sunscreen (Daemonorops draco (Willd.) Blume) as an antioxidant and ultraviolet (UV) protector - Nasela, Tiara; Lestari, Uce; Asra, Revis (Riset Informasi Kesehatan, 2025)
Background: Prolonged exposure to ultraviolet (UV) radiation from sunlight can cause various skin problems, including sunburn, hyperpigmentation, and premature aging. Natural-based sunscreens are an innovative alternative to synthetic sunscreens, which may have side effects such as irritation and allergic reactions. Dragon’s blood (Daemonorops draco (Willd.) Blume) is known for its strong antioxidant properties due to its flavonoid content, particularly dracorhodin, which has the potential to be formulated as a sunscreen. This study aims to evaluate the clinical effectiveness of jernang resin sunscreen in providing UV protection and improving skin moisture and brightness. Method: A clinical trial was conducted involving 30 volunteers aged 18–50 years with normal skin and no history of allergies or skin diseases. The study included irritation tests, hedonic evaluations, skin brightness assessments, moisture level analysis using a Skin Analyzer, and UV protection effectiveness using a UV Camera over 30 days. The statistical analysis was performed using One-Way ANOVA and Duncan's test for significant differences. Results: The results showed that the jernang resin sunscreen exhibited significant UV protection, maintaining its effectiveness for 30 days. It also enhanced skin moisture and brightness compared to the control group. The hedonic test revealed high acceptability regarding color, texture, and aroma. The irritation test indicated no significant adverse reactions, confirming the product's safety. Conclusion: Dragon’s blood sunscreen has demonstrated excellent potential as an effective and safe natural alternative for UV protection, with added benefits of improving skin hydration and brightness. Further research is recommended to optimize its formulation for commercial use.